Status of the buffalo milk trade and dairy manufacturing business at Bhola district of Bangladesh, and opportunities for buffalo milk products branding - Habib, Md Rezwanul; Hasan Khandakar, Md Mehedi; Islam, Md Ariful; Sarkar, Md Moznu; Alam, Mohammed Khorshed; Rahman, Md Khalilur; Sharmin, Mst Mamuna; Hannan, Mohammad Mazedul; Islam, Mohammad Ashiqul (Research in Agriculture Livestock and Fisheries, 2022)
The objective of this study was to know the existing buffalo milk trade and dairy products production status along with scope for buffalo milk product branding. Hence, a face-to-face interview with eighteen milk traders and processors were performed through simple random sampling method. Milk traders and processors were above 25 years old (94%) and above 5 years (89%) experienced in dairy business. The findings exposed that 11% of the participants were involved in milk collection and selling, 39% were directly involved in product manufacturing, and 50% were engaged in milk collection and processing. Among the manufactured dairy products, traditionally made fermented doi was the best - selling dairy product in the Bhola district. About 47% participants desired to incorporate fat-rich dairy products into their production processes. In general, milk traders sold the maximum amount of milk monthly to doi manufacturers (1453 L), followed by local customers (1175 L), sweetmeat manufacturers (1000 L), restaurants (257 L), and household consumers (250 L). Results showed that buffalo milk prices varied significantly (P<0.001) over the year. The peak buffalo milk price (122 BDT/L) was recorded between November and December, and the off-peak price (82 BDT/L) was between March to May. Data indicated that about 43-50 BDT profit derived through per kg doi and sweetmeat selling. Milk traders and processors mentioned that studied areas had greater shortage of milk preservation facilities. Overall, the findings of this study may give some context for developing sustainable buffalo milk and dairy products value chain in Bangladesh. Res. Agric., Livest. Fish.8(3): 301-310, December 2021